Dysregulated bile acid receptor-mediated signaling and IL-17A induction are implicated in diet-associated hepatic health and cognitive function - Prasant Kumar Jena; Lili Sheng; Michelle Nguyen; Jacopo Di Lucente; Ying Hu; Yongchun Li; Izumi Maezawa; Lee-Way Jin; Yu-Jui Yvonne Wan (BMC, 2020)
Abstract Background Chronic consumption of high sugar and high fat diet associated with liver inflammation and cognitive decline. This paper tests a hypothesis that the development and resolution of diet-induced nonalcoholic fatty liver disease (NAFLD) has an impact on neuroplasticity and cognition. Methods C57BL/6 wild-type mice were fed with either a healthy control diet (CD) or a fructose, palmitate, and cholesterol (FPC)-enriched diet since weaning. When mice were 3-months old, FPC diet-fed mice were randomly assigned to receive either FPC-enriched diet with or without 6% inulin supplementation. At 8 months of age, all three groups of mice were euthanized followed by analysis of inflammatory signaling in the liver and brain, gut microbiota, and cecal metabolites. Results Our data showed that FPC diet intake induced hepatic steatosis and inflammation in the liver and brain along with elevated RORγ and IL-17A signaling. Accompanied by microglia activation and reduced hippocampal long-term potentiation, FPC diet intake also reduced postsynaptic density-95 and brain derived neurotrophic factor, whereas inulin supplementation prevented diet-reduced neuroplasticity and the development of NAFLD. In the gut, FPC diet increased Coriobacteriaceae and Erysipelotrichaceae, which are implicated in cholesterol metabolism, and the genus Allobaculum, and inulin supplementation reduced them. Furthermore, FPC diet reduced FXR and TGR5 signaling, and inulin supplementation reversed these changes. Untargeted cecal metabolomics profiling uncovered 273 metabolites, and 104 had significant changes due to FPC diet intake or inulin supplementation. Among the top 10 most affected metabolites, FPC-fed mice had marked increase of zymosterol, a cholesterol biosynthesis metabolite, and reduced 2,8-dihydroxyquinoline, which has known benefits in reducing glucose intolerance; these changes were reversible by inulin supplementation. Additionally, the abundance of Barnesiella, Coprobacter, Clostridium XIVa, and Butyrivibrio were negatively correlated with FPC diet intake and the concentration of cecal zymosterol but positively associated with inulin supplementation, suggesting their benefits. Conclusion Taken together, the presented data suggest that diet alters the gut microbiota and their metabolites, including bile acids. This will subsequently affect IL-17A signaling, resulting in systemic impacts on both hepatic metabolism and cognitive function.